Implantação de Reservas Legais: uma nova perspectiva na conservação dos recursos naturais em paisagem rural - Destro, Guilherme F. G. [UNESP]; Campos, Sérgio [UNESP] (Universidade Federal da Paraíba (UFPB) Ccsa, 2010)
According to the Forest Code of 1965, it is mandatory that every rural property destine part of its land to the establishment of Legal Reserves. When a diagnosis is made over all Brazil, the reality is quite different from what is demanded by law. Therefore, this work, as a general objective, proposes ways of establishing Legal Reserves based on the analysis of the environmental deterioration in a river basin. For this purpose, the environmental deterioration was detected based on three diagnoses: physical-conservational, socioeconomical, and environmental quality. In this way, from a quantitative and qualitative diagnosis, it was possible to identify the main aggressive factors in the studied river basin and to indicate the main vulnerabilities that the area is subjected. According to such diagnosis, some proposals for the establishment of Legal Reserves are discussed here based on scientific arguments aimed at the conservation of water resources, soil and biodiversity. It is hoped, that from this study, the environment receives a new tool for diagnosis, pollution control, recovery and conservation of natural resources.
Implantation of Legal Reserves: A new perspective in the conservation of the natural resources in rural landscapes
Keywords: GIS-SPRING; geoprocessing; remote sensing; environmental deterioration